Dickinson Lectures in Accounting/Improvement in Financial Accounts (Book). - Winter, Sidney G. (The Accounting Review, 1944)
Abstract Reviews two books on accounting. "Dickinson Lectures in Accounting," by George O. May, Laurence Halsey and William A. Paton; "Improvement in Financial Accounts," by George O. May.